Operational Risks in the Banking Industry (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The goal of this paper is to point out the current situation in the banking sector related to its risks (credit risk, market risk, liquidity risk, concentration risk) with a special emphasis on today’s one of the major types of banking risk, the operational risk. This phrase contains the risks of losses which could happen due to the inadequacy of internal processes, human errors, poor implementation of information systems or possible risky external events, so legal risks are also often included in the definition of operational risks. In this paper the tools to identify and evaluate those risks, capital requirements for operational risk and finally the role of supervisors in managing these types of risks will be given.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.